AGRARIAN REFORM POLICY IMPLEMENTATION (Study on the Role of the Indonesian National Land Office of Palu City) - Ano, Jusuf; Daswati, Daswati; Ahsan, Sitti Chaeriah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Agrarian reform is the best idea ever born in order to overcome land problems and natural resource management problems. The purpose of the study was to determine the role of the Indonesian National Land Office of Palu City in agrarian reform. Qualitative research method, withdrawal of informants through purposive sampling and data analysis techniques using the Miles & Huberman model, namely Data Collecting, Data reduction, Data Display, verifying / conclusion.The results showed that (a) Regulator. The active role of the Indonesian National Land Office of Palu City in the implementation of agrarian reform is measured through the role, (b) Facilitator. The Agrarian Reform Village Pilot Project is one of the joint programs of the Collaboration of Regional Apparatus Organizations that are members of the Palu City Agrarian Reform Task Force team, (c) Catalyst. This role is intended by conducting training and socialization to the community in whose area the agrarian reform policy is implemented, in this case the sub-district, (d) Innovator. Innovation in the implementation of agrarian reform largely seeks the welfare of the community with various potentials of the region and (e) Implementers. The implementers of the agrarian reform policy implementation in Palu City are those who are closely related to the execution or implementers of government policies, namely: Indonesian National Land Office of Palu City. The implementation of agrarian reform is carried out through the stages of Asset Reform and Access Reform